2004
DOI: 10.1136/adc.2003.047258
|View full text |Cite
|
Sign up to set email alerts
|

Survey of administration of medicines to pupils in primary schools within the London area

Abstract: Objective: To examine the policy, administration, and supervision of medicine administration in primary schools within the Greater London area (GLA). Design: A prospective survey using postal questionnaires sent to 172 randomly selected primary schools within the GLA. Participants: Head teachers of primary schools. Results: Some 65% of head teachers replied. Less than 50% of responding head teachers had actually read the national guidelines Supporting Pupils with Medical Needs and only 30% of respondents were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 6 publications
2
12
0
Order By: Relevance
“…A survey of 111 primary schools in the London area in 2003 (Wong et al . 2004b) reported 67% of school head teachers were aware of the national guidance, but that only 47% had read the documents.…”
Section: Resultsmentioning
confidence: 99%
“…A survey of 111 primary schools in the London area in 2003 (Wong et al . 2004b) reported 67% of school head teachers were aware of the national guidance, but that only 47% had read the documents.…”
Section: Resultsmentioning
confidence: 99%
“…In a survey of London primary school head teachers,6 95% reported having a policy relating to the medical needs of young people and 50% had individual care plans in place for specific conditions, as advocated by the Department of Education and Employment 5. In County Durham, a survey involving 296 head teachers7 revealed that all secondary schools and two fifths of primary schools had a policy relating to asthma.…”
mentioning
confidence: 99%
“…[3,4] However, the presence of a fulltime school nurse is limited and medicines often have to be administered by teachers, auxiliary staff and secretaries. [5][6][7] This represents a challenge for school staff, who do not have medical qualifications. As a result, schoolchildren with special health care needs may experience difficulties in their medication management, and may not receive optimum support for the proper treatment of their condition.…”
Section: Introductionmentioning
confidence: 99%